Scientific literacy on peatland across various study programs, genders, and current domicile of University Students in Borneo - Sidauruk, Suandi; Ni'mah, Fatchiyatun; Meiliawati, Ruli; Analita, Rizki Nur; Rahmadani, Agung; Budi, Firman Shantya; Adhani, Aidhil (Intelektual Pustaka Media Utama, 2025)
Scientific literacy is the ability that students must have to analyze and apply science concepts in solving everyday life problems. Students’ scientific literacy on peatlands can be acquired by students from daily interaction with peatlands, understanding that comes from parents and the community, as well as from learning in the classroom. This study aims to analyze the scientific literacy skills of students from several campuses in Borneo on the topic of peatlands. In this study, scientific literacy is described into scientific knowledge and scientific competencies domain. The research was conducted using a survey method with 528 respondents from several universities in Borneo, Indonesia. Research results show that even half of the respondents live around the peatland area, students’ scientific literacy is in the low category. The students’ scientific competencies need serious attention. A proper learning resources and comprehensive learning is needed to improve student overall scientific literacy.